Effects of Short-Term Corticosteroid Use on Reactogenicity and Immunogenicity of the First Dose of ChAdOx1 nCoV-19 Vaccine - Yang, Jinyoung; Ko, Jae-Hoon; Baek, Jin Yang; Hong, Jinyeong; Ha, Soyoung; Lee, Beomki; Huh, Kyungmin; Cho, Sun Young; Kang, Cheol-In; Chung, Doo Ryeon; Kim, Yae-Jean; Kang, Eun-Suk; et al. (Frontiers in Immunology, 2021)
The effects of corticosteroid use on the reactogenicity and immunogenicity of ChAdOx1 nCoV-19 (ChAd) vaccine were evaluated. Healthcare workers (HCWs) who took low-dose corticosteroid agents around the time of the first dose of ChAd (ChAdPd group) were recruited and the reactogenicity and immunogenicity were compared with those of ChAd (ChAd group) and BNT162b2 vaccination (BNT group) of HCWs without corticosteroid exposure. The immunogenicity was measured three weeks after vaccination using quantitative anti-SARS-CoV-2 spike protein (S) antibody electrochemiluminescence immunoassay and interferon gamma (IFN-γ) release assay. A total of 67 HCWs comprising 24 ChAd, 29 BNT, and 14 ChAdPd was included. The median total corticosteroid dose of the ChAdPd group was 30 mg prednisolone equivalents (interquartile range (IQR) 20–71.3 mg). HCWs in the ChAdPd group experienced significantly milder reactogenicity (median total score 7.5, IQR 4.0–18.0) compared to those in the ChAd group (median 23.0, IQR 8.0–43.0, P=0.012) but similar to that in the BNT group (median 5.0, IQR 3.0–9.0, P=0.067). The S antibody concentration of the ChAdPd group (62.4 ± 70.0 U/mL) was higher than that of the ChAd group, though without statistical significance (3.45 ± 57.6 U/mL, P=0.192). The cellular immune response was most robust in the ChAdPd group, with significantly higher IFN-γ concentration (5.363 ± 4.276 IU/mL), compared to the ChAd (0.978 ± 1.181 IU/mL, P=0.002) and BNT (1.656 ± 1.925 IU/mL, P=0.009) groups. This finding suggest that short-term corticosteroid reduces reactogenicity of the first dose of ChAd without hindering immunogenicity.